Field research 2009 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Includes research reports from these locations: East Central Kansas Experiment Field, Kansas River Valley Experiment Field, Harvey County Experiment Field, Irrigation and North Central Kansas Experiment Fields, South Central Kansas Experiment Field, and Western Kansas Agricultural Research Centers.
Keywords: Kansas; Agriculture; Crops; Weed control; Disease control; Fertilizer; Irrigation